HMB-45 - A review - Bacchi, C. E.; Bonetti, F.; Pea, M.; Martignoni, G.; Gown, A. M. (Lippincott-raven Publ, 1996)
HMB-45, named for the immunogen used (human melanoma, black) is a monoclonal antibody developed 10 years ago by Gown and colleagues to a whole-cell extract of a human melanoma. Over the years, it has been demonstrated that HMB-45 is a highly sensitive and specific reagent for the identification of melanoma. More recently, it has been found that HMB-45 reacts with a protein designated gp100-cl, which is apparently related to the pmel 17 gene product. Because gp100-cl is a melanosomal matrix protein, HMB-45 is more correctly identified as an organelle-specific rather than tumor-specific reagent. HMB-45 immunoreactivity is seen in normal fetal and neonatal melanocytes but not in adult resting melanocytes. Reactive or proliferating melanocytes present in inflamed adult skin or in skin overlying certain dermal neoplasms, can also ''re-express'' the HMB-45-defined antigen. Whereas the vast majority of melanomas are HMB-45-positive, one important exception is desmoplastic malignant melanoma, which consistently demonstrates a much lower rate of expression of the HMB-45-defined antigen compared with other types of melanoma. In recent years there have been scattered reports of HMB-45 immunoreactivity in nonmelanomatous tumors, such as breast and other carcinomas, but virtually all these reports employed commercial ascites fluid preparations of HMB-45 antibody that were subsequently shown to be contaminated with nonspecific antibodies. Thus, for most practical purposes, a positive reaction with HMB-45 indicates active melanosome formation and, therefore, melanocytic differentiation. There is also a set of HMB-45-positive tumors that consistently manifest HMB-45 immunoreactivity but do not display obvious pigmentation: clear cell ''sugar'' tumor of the lung, angiomyolipoma, and lymphangiomyomatosis. Nonetheless, these lesions are all unified by recent ultrastructural studies that confirm the presence premelanosomes. Curiously, all three lesions also manifest evidence for simultaneous smooth-muscle differentiation. HMB-45 remains, therefore, a reliable marker of melanoma but may also provide insights into a rare group of tumors.
Keywords: HMB-45; melanoma; immunohistochemistry; melanosomes; angiomyolipoma; sugar tumor; lymphangiomyomatosis; tuberous sclerosis